Association between self-rated health and physical activity among physician assistants in Ghana: a cross-sectional study - Akwaboah, Patrick K.; Larweh, Richmond; Somuah, Akosua A.; Baah, George; Ntiri, Kofi Adjei (International Journal Of Community Medicine And Public Health, 2025)
Background: Self-rated health (SRH) has been a subjective measure of health, yet its association with physical activity (PA) among healthcare workers in sub-Saharan Africa remains underexplored. This study examined the association between SRH and PA [leisure-time physical activity (LTPA) and active transportation (AT)] among Physician Assistants in Ghana. Methods: A cross-sectional study involving 439 licensed Physician Assistants was conducted between October and December 2024 using an online survey. Multivariate logistic regressions modelled the association between SRH and PA, using adjusted odds ratios (aOR) and 95% confidence intervals (CIs) and controlling for sociodemographic, work-related, environmental and psychological factors. Results: Overall, 18.7% of PAs reported poor SRH. Participants in the third quartile of LTPA had the highest odds of good SRH (aOR=3.36, 95% CI: 1.58–7.16), though a plateau effect was observed at higher activity levels. AT to and from work was significantly associated with good SRH (aOR=2.32 and 2.16, respectively). Anxiety, older age, lower income, lower rank and poor environmental conditions were associated with reduced odds of good SRH. The availability of sidewalks showed a strong positive association with good SRH. Gender differences in PA domains were also observed, with males being significantly more active than females. Conclusions: Engagement in moderate LTPA and active commuting is associated with good SRH among Ghanaian Physician Assistants. Interventions to increase physical activity may enhance health outcomes in this vital health workforce. Longitudinal studies are needed to establish causal relationships and inform policy.